THE EFFECT OF WORK ENVIRONMENT AND ORGANIZATIONAL CLIMATE ON CITIZENSHIP ORGANIZATIONAL BEHAVIOR WITH JOB SATISFACTION AS A PRIVATE VARIABLE IN THE YOGYAKARTA DEPARTMENT OF TRANSPORTATION - Rengga Sukma Subastono; Prayekti Prayekti; I. Soni Kurniawan (JURNAL TERAPAN MANAJEMEN DAN BISNIS, 2023)
This study aims to determine the effect of work environment and organizational climate on the behavior of organizational citizenship with job satisfaction as a mediator. The population used in this study consisted of employees of the Yogyakarta Department of Transportation, the sampling method was saturated sampling (census). The information was collected through questionnaires that were distributed to employees. The number of questionnaires processed was 51 questionnaires. Data were analyzed using multiple linear regression analysis. The results showed that the work environment had a positive and significant effect on job satisfaction. The organizational climate has a positive and significant effect on job satisfaction. The work environment has no positive and significant effects on organizational citizenship behavior. The organizational climate has a positive and significant effect on organizational citizenship behavior. There is no significant effect of the work environment on organizational citizenship behavior with job satisfaction as a mediating variable. There is no significant effect of the organizational climate on the behavior of organizational citizenship with job satisfaction as a mediating variable.